Analysis of self medication practice among medical undergraduates: a study in tertiary care teaching hospital, Bareilly - Bhardwaj, Richa; Sayedda, Kauser; Ahmed, Quazi Shahir (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Self medication is becoming a most prevalent practice among educated people across the world. In today’s era, internet and media is one of the most important sources for promoting self medication practice. Medical students are highly influenced with this practice. Many drugs can have significant unwanted effects. This may result in serious clinical effects with potential life-threatening complications. Objective of the study was to find out the self medication practice and its details among medical undergraduates of SRMSIMS, a tertiary care teaching hospital, Bareilly. Methods: During the study period 1st, 2nd and 3rd prof. of MBBS students were included in the study. Sample size was 348. They were asked to fill printed semi structured validated questionnaire which consist of straight forward multiple type questions. The duration of study was March 22nd 2015 to 29th March 2015. Results: Out of 300 students, 60% (n=180) students were male and 40% (n=120) were females. Among them 94% (n=282) gave positive response and 6% (n=18) gave negative response to self-medication. Antibiotics were the most common class of drug self medicated by the majority of participants (80%) while the most common illness was fever (70%). Conclusions: It was concluded that more than half of strength of students are likely to take self-medication for various illnesses; the reason might be the awareness of drugs due to easy accessibility of information through books, internet pharmacy and through media too. So, essential measure should be taken to reduce the practice of self medication among students to avoid development of drug dependence, resistance and drug interactions.